PERILAKU PENGGUNAAN DAN PERAWATAN KELAMBU LLINs PADA MASYARAKAT DAERAH ENDEMIS MALARIA KABUPATEN LEBAK PROVINSI BANTEN - Diana Andriyani Pratamawati; Siti Alfiah; Widiarti Widiarti (Balai Besar Penelitian dan Pengembangan Vektor dan Reservoir Penyakit (B2P2VRP) Salatiga, 2018)
The effectiveness of insecticide-treated nets are believed to reduce the prevalence of malaria is influenced by the behavior of people in their use , such as how to install and wash , in addition to duration of use . People's behavior can be different in each region with respect to culture , culture and ethnicity / ethnicity as a predisposing factor . The purpose of this study is to describe the behavior of people in the use of insecticide-treated nets ( LLINs ), such as the acceptance, use, washing and participation in the care of LLINs (program preservation).The study design was observational cross-sectional design. The instrument of this research is questionnaire and observation guidance of mosquito net. Samples are people with insecticide-treated nets in Lebak regency (Banten) were 81 respondents . Data were analyzed by descriptive. The results showed the level of knowledge about the use of mosquito nets in the category of